2018
DOI: 10.1016/j.jmapro.2018.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tool geometry and welding speed on mechanical properties of dissimilar AA2198–AA2024 FSWed joint

Abstract: Keywords:Friction stir welding FSW tool design Al-Li alloys Welding speed 2024 aluminum alloy Tensile properties DIC A B S T R A C T Different tool geometries were used to investigate the joining of aluminum alloys (AA2198 to AA2024) by friction stir welding (FSW). Three shoulder profiles (flat, raised spiral, and raised fan) and five different pin profiles (cone, half threaded cylindrical, straight cylindrical, tapered cylindrical and square) were selected. Preliminary investigations were conducted by moving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…The weakening of AS interface has been widely investigated. Texier et al 45 observed higher strain between SZ and TMAZ of AS of the AA2024‐AA2198 dissimilar FSW joint. They indicated that the local macroscopic strain localization leading to necking and failure was closely related to local crystallographic orientation heterogeneities.…”
Section: Resultsmentioning
confidence: 95%
“…The weakening of AS interface has been widely investigated. Texier et al 45 observed higher strain between SZ and TMAZ of AS of the AA2024‐AA2198 dissimilar FSW joint. They indicated that the local macroscopic strain localization leading to necking and failure was closely related to local crystallographic orientation heterogeneities.…”
Section: Resultsmentioning
confidence: 95%
“…This is because the larger shoulder (i.e., larger taper angle being the tool tip diameter always 4 mm for all the pins) of tool T1 increases friction between tool and sheets, thus generating high temperatures in weld and the consequent formation of thick IMCs. Khalilabad et al [51] investigated the effects of tool geometry on FSW joint quality. They found that conical and threaded cylindrical pins had the tendency to result in defective joints with kissing bond, tunnel, and flash, as compared to cubical, cylindrical, and tapered cylindrical pins.…”
Section: Tool Geometrymentioning
confidence: 99%
“…In both cases, limited capability of metal intermixing led to the occurrence of welding defects. Khalilabad et al [51] investigated the effects of tool geometry on FSW joint quality. They found that conical and threaded cylindrical pins had the tendency to result in defective joints with kissing bond, tunnel, and flash, as compared to cubical, cylindrical, and tapered cylindrical pins.…”
Section: Tool Geometrymentioning
confidence: 99%
“…Giraud et al (2016) noticed the influence of the process parameters on material mixing, weld integrity, and mechanical behavior. Masoumi Khalilabad et al (2018) observed that increasing the traverse speed of the tool increases the global hardness of the joint, but also creates defects like a kissing bond, in the case of an AA2198/AA2024 FSWed joint.…”
Section: Introductionmentioning
confidence: 99%